Dampak Eksternalitas PT. Sipef Bukit Maraja terhadap Kondisi Sosial Ekonomi Masyarakat di Desa Bukit Maraja Kabupaten Simalungun - Salman Salman; Nurlaila Hanum; Puja Silvia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to see and analyze the impact of PT Sipef Bukit Maraja’s externalities on the socio-economic conditions of the Bukit Maraja village community. The research uses primary data obtained from distributing questionnaires. Data collection used random sampling technique with a total of 94 respondents. The model used in this research is a quantitative descriptive statistical analysis method with results measurement using the SPSS program and Likert scale measurements. The research results show that the impact on social aspects has a score of 56.6% in the neutral category, which means that PT Sipef has no impact on the social aspects of society. Furthermore, in the economic aspect, a score of 79% was obtained, which means that it agrees that the existence of PT Sipef has a positive impact on the economic aspect of society. The research results show that calculations from both aspects, namely social and economic, were obtained the total frequency index score was 67.65% with the agree category which concluded that the existence of PT Sipef Bukit Maraja had a positive impact on the socio-economics of the Bukit Maraja village community.